Competences, characteristics and institutional environment of educators at children shelters - Serrano Arias, Martha E. (Consorcio de Universidades Mexicanas A.C., 2012)
In Mexico, shelters for abused or neglected children are required to guarantee minimum levels of wellbeing (Gobierno de México, 2002). The work that educators engage in at these shelters is very important and has to be qualified and supervised (Gobierno de Brasil, 2007). Regarding this matter, the theory of Social Education stresses the relevance of an educator as someone who is able to taking care of vulnerable groups like children and teenagers (AIEJI, 2007). Therefore, the objective of this study was to analyze the educators’ competency, their personal characteristics, and institutional environment at public and private shelters in Hermosillo, Sonora, Mexico. One hundred-and-seventeen educators at seven institutions devoted to shelter abused or poor children participated in the study. The instrument was an evaluation scale based on the established indicators of the White Book for a degree in Pedagogy and Social Education (Libro Blanco, ANECA, 2005). The participants were interviewed in the shelters they worked at. Univariate statistics, Cronbach’s alphas and correlations were obtained to analyze the data. Language & reasoning resulted significantly correlated with educative functions (.26) and with commitment with own identity (26); satisfaction of needs and commitment also resulted significantly related to own identity (.22) and to language and reasoning (.39). One more significant correlation resulted between schooling and interpersonal abilities (26). Age was correlated with time on the job (.48), schooling (-.19), satisfaction of needs (.25) and language and reasoning (.19). These results show the importance of institutional environments in the development of educational functions and institutional commitment of educators